The essence of the heirs’ obligation to reimburse funeral expenses of the testator and peculiarities of its fulfilment - O. Ye. Kukhariev (Law and Safety)
The article is aimed at clarifying the essence of the heirs' obligation to reimburse the funeral expenses of the testator and the specifics of its fulfilment. It has been noted that the specified obligation is not an element of the inheritance, and therefore the provisions of Articles 1281 and 1282 of the Civil Code of Ukraine, that define the claims of the testator's creditor against the heirs and the obligation of the heirs to satisfy the creditor's claims, are not applied in its fulfilment. It has been concluded that payment for the funeral of the testator gives rise to a non-contractual binding legal relationship in which the creditor is the person who incurred the relevant expenses, and the debtor is the heir, provided that he or she accepts the inheritance. Such an obligation arises only if the creditor has paid his or her own funds for the funeral of the deceased and if these costs are reasonable. Payment of funeral expenses by one of the heirs is not a ground for increasing the size of the inheritance share of that heir. They can only raise the issue of partial reimbursement of the expenses.